2018
DOI: 10.1016/j.reprotox.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and nutritional status of trace elements in hair of women with in vitro fertilization (IVF) pregnancy and their 9-month-old children

Abstract: Skalny, Anatoly V.; Tinkov, Alexey A.; Bohan, Tatiana G.; Shabalovskaya, Marina B.; Terekhina, Olga; Leshchinskaia, Svetlana B.; Agarkova, Lyubov A.; Notova, Svetlana V.; Skalnaya, Margarita G. and Kovas, Yulia. 2018. Toxicological and nutritional status of trace elements in hair of women with in vitro fertilization (IVF) pregnancy and their 9-month-old children. Reproductive Toxicology, 82, pp. 50-56. ISSN 0890-6238 [Article]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Two periods of a significant increase in the level of these metals in bio substrate were found: the first between 2 and 9 years of age; the second is from 60 to 85 years. Unfortunately, the quantitative shifts of other metals were not analyzed, although in children aged 2-9 years they could be identical to those given by the authors of the study in question [1] Table 2.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Two periods of a significant increase in the level of these metals in bio substrate were found: the first between 2 and 9 years of age; the second is from 60 to 85 years. Unfortunately, the quantitative shifts of other metals were not analyzed, although in children aged 2-9 years they could be identical to those given by the authors of the study in question [1] Table 2.…”
Section: Introductionmentioning
confidence: 75%
“…
The present article comments on the results of hair spectrometry in pregnant and 9-month-old babies born to these women published in the Reproductive Toxicology journal ( 2018) [1]. The author of this article gives a different explanation of the data obtained by the aforesaid study in view of the idea of metal-ligand homeostasis in the epidermis as a self-organized criticality phenomenon.
…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Five studies ( 23 , 26 , 29 31 ) investigated heavy metals and metalloids in hair samples of women undergoing IVF. In a study to examine the heavy metals and metalloids status in hair samples of women with IVF pregnancy and their 9-month-old children, Skalny et al ( 29 ) found out that women with IVF pregnancy demonstrated significantly high hair As, Hg, Li levels and their children also had significantly elevated hair Hg and Mo concentrations compared to control ( 30 ). Similarly, another case-control study by Skalny et al ( 30 ) demonstrated that IVF pregnancy correlated significantly with elevated hair levels of As ( p < 0.05) suggestive of arsenic overload in IVF patients ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other trace elements and minerals including copper, magnesium [20], iron [21], calcium [22], also play a role in normal pregnancy and fetal development. A significant relationship has been demonstrated between trace element status and risk of infertility [23], as well as pre-eclampsia [24] and other adverse outcomes [25]. It has been also noted that altered trace element status may be also involved in pathogenesis of postpartum depression [26].…”
Section: Introductionmentioning
confidence: 99%